Care of 500–1500 Gram Premature Infants in Hybrid Incubators. (October 2017) - Boyd, Holly; Brand, M. Colleen; Hagan, Joseph
Abstract : Background: Although technological advances have improved devices used to maintain the temperatures of 500- to 1500-g infants, managing the thermal environment remains challenging. Purpose: To evaluate the effects of 2 methods of thermal support provided by a hybrid incubator during routine care in the first week of life. Methods: This descriptive, comparative study evaluates changes in temperature, humidity, heart rate, and oxygen saturation in the incubator versus radiant warmer (canopy) modes of hybrid warmers using data downloaded from the incubator and the monitor. The impact of the Boost Curtain on temperature when opening the portholes during the incubator mode was also examined. Mixed-effects linear models and the log-rank test were used to analyze patient data to determine the effect of thermal support on temperature and humidity changes during care, as well as during the postcare period. Results: Entering the incubator through the portholes improved temperature control compared with using the canopy mode. The Boost Curtain resulted in an overall temperature stability and heat gain. Implications for Practice: Nurses caring for premature infants in hybrid incubators should minimize incubator openings and utilize portholes rather than the canopy whenever practical. The Boost Curtain should be used when opening the portholes during the incubator mode. Implications for Research: Comparing time, accuracy, and tolerance of procedures in the canopy versus incubator modes would improve nurses' ability to determine the best approach for different clinical scenarios.